Transitioning from child to adult mental health services: what role for social services? Insights from a European survey. Issue 3 (15th September 2020) - Signorini, Giulia; Davidovic, Nikolina; Dieleman, Gwen; Franic, Tomislav; Madan, Jason; Maras, Athanasios; Mc Nicholas, Fiona; O'Hara, Lesley; Paul, Moli; Purper-Ouakil, Diane; Santosh, Paramala; Schulze, Ulrike; et al.
Abstract : Purpose: Young people transitioning from child to adult mental health services are frequently also known to social services, but the role of such services in this study and their interplay with mental healthcare system lacks evidence in the European panorama. This study aims to gather information on the characteristics and the involvement of social services supporting young people approaching transition. Design/methodology/approach: A survey of 16 European Union countries was conducted. Country respondents, representing social services' point of view, completed an ad hoc questionnaire. Information sought included details on social service availability and the characteristics of their interplay with mental health services. Findings: Service availability ranges from a low of 3/100, 000 social workers working with young people of transition age in Spain to a high 500/100, 000 social workers in Poland, with heterogeneous involvement in youth health care. Community-based residential facilities and services for youth under custodial measures were the most commonly type of social service involved. In 80% of the surveyed countries, youth protection from abuse/neglect is overall regulated by national protocols or written agreements between mental health and social services, with the exception of Czech Republic and Greece, where poor or no protocols apply. Lack of connection between child and adult mental health services has been identified as the major obstacles to transition (93.8%), together with insufficient involvement of stakeholders throughout the process. Research limitations/implications: Marked heterogeneity across countries may suggest weaknesses in youth mental health policy-making at the European level. Greater inclusion of relevant stakeholders is needed to inform the development and implementation of person-centered health-care models. Disconnection between child and adult mental health services is widely recognized in the social services arena as the major barrier faced by young service users in transition; this "outside" perspective provides further support for an urgent re-configuration of services and the need to address unaligned working practices and service cultures. Originality/value: This is the first survey gathering information on social service provision at the time of mental health services transition at a European level; its findings may help to inform services to offer a better coordinated social health care for young people with mental health disorders.